THE ROLE OF COMMUNICATION IN LEARNING ENGLISH AND CHINESE AMONG STUDENTS - Suyarova Xolisa Azamat qizi,; Razzaqova Shaxlo Baxtiyorovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article analyzes the importance of communication in learning English and Chinese among students. The study highlights the role of communicative approaches in foreign language acquisition and examines their influence on students’ linguistic competence, intercultural communication, academic achievement, and professional development. The article also discusses the role of modern technologies and international educational programs in creating communicative environments for language learning. The findings show that communication-based education significantly improves students’ practical language skills and learning motivation.